Micro-minicircle Gene Therapy: Implications of Size on Fermentation, Complexation, Shearing Resistance, and Expression - Sofia Stenler; Oscar PB Wiklander; Maria Badal-Tejedor; Janne Turunen; Joel Z Nordin; David Hallengärd; Britta Wahren; Samir EL Andaloussi; Mark W Rutland; CI Edvard Smith; Karin E Lundin; Pontus Blomberg (Elsevier, 2014)
The minicircle (MC), composed of eukaryotic sequences only, is an interesting approach to increase the safety and efficiency of plasmid-based vectors for gene therapy. In this paper, we investigate micro-MC (miMC) vectors encoding small regulatory RNA. We use a construct encoding a splice-correcting U7 small nuclear RNA, which results in a vector of 650 base pairs (bp), as compared to a conventional 3600 bp plasmid carrying the same expression cassette. Furthermore, we construct miMCs of varying sizes carrying different number of these cassettes. This allows us to evaluate how size influences production, super-coiling, stability and efficiency of the vector. We characterize coiling morphology by atomic force microscopy and measure the resistance to shearing forces caused by an injector device, the Biojector. We compare the behavior of miMCs and plasmids in vitro using lipofection and electroporation, as well as in vivo in mice. We here show that when the size of the miMC is reduced, the formation of dimers and trimers increases. There seems to be a lower size limit for efficient expression. We demonstrate that miMCs are more robust than plasmids when exposed to shearing forces, and that they show extended expression in vivo.